Innovation , Business , Education – Regional , National and European Policies 2020 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This report examines the choice of innovation strategy, which is based on an analysis of the innovation capacity of the region in: innovation, business and education. Set is a set of features that facilitate and support innovation. The purpose of the analysis is to identify the main features and to what extent they have.